The Legal Relationships Arising from Childcare in the Orphanages of Al-Hikmah Sejalan Cangkringan - Hasanah, Arina Jazaiyatun; Musjtari, Dewi Nurul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Every parent has the intention to provide a better future and prosperous life to their children, but not everyone can do them, and there are many ways to solve it, one of them is by entrusting their children to an orphanage. The purpose of this study was to determine the legal relationships arising from childcare for the welfare of children and whose the parties are responsible for the welfare of children at the Orphanage of Al-Hikmah Sejalan Cangkringan. The research method used to complete this research is empirical normative method using primary and secondary data through qualitative data collection and compiled descriptively. The result of this research is that the existence of a legal relationship between foster children and the Al-Hikmah Orphanage is only limited to the relationship of a foundation that provides childcare assistance, there is no guardianship between two parties but there is a kafalah that foster children get welfare in the form of a place to live, affection, education, daily necessities and the party responsible for the welfare of the children in the orphanage is the manager and care giver as the main responsibility with the help of the wider community. Research on the legal consequences of childcare is still not paid attention by many researchers, as well as about the legal relationship between foster children and the orphanage. Therefore the author wants to dig deeper into the importance of the legal relationship that exists in the orphanage with this research.